Ultrafast photodriven intramolecular electron transfer from an iridium-based water-oxidation catalyst to perylene diimide derivatives - Vagnini, Michael T. (National Academy of Sciences, 2012)
Photodriving the activity of water-oxidation catalysts is a critical step toward generating fuel from sunlight. The design of a system with optimal energetics and kinetics requires a mechanistic understanding of the single-electron transfer events in catalyst activation. To this end, we report here the synthesis and photophysical characterization of two covalently bound chromophore-catalyst electron transfer dyads, in which the dyes are derivatives of the strong photooxidant perylene-3,4:9,10-bis(dicarboximide) (PDI) and the molecular catalyst is the Cp(∗)Ir(ppy)Cl metal complex, where ppy = 2-phenylpyridine. Photoexcitation of the PDI in each dyad results in reduction of the chromophore to PDI(•-) in less than 10 ps, a process that outcompetes any generation of (3∗)PDI by spin-orbit-induced intersystem crossing. Biexponential charge recombination largely to the PDI-Ir(III) ground state is suggestive of multiple populations of the PDI(•-)-Ir(IV) ion-pair, whose relative abundance varies with solvent polarity. Electrochemical studies of the dyads show strong irreversible oxidation current similar to that seen for model catalysts, indicating that the catalytic integrity of the metal complex is maintained upon attachment to the high molecular weight photosensitizer.